Serum prolidase enzyme activity in obese subjects and its relationship with oxidative stress markers - Aslan, Mehmet; Duzenli, Ufuk; Esen, Ramazan; Soyoral, Yasemin Usul (Clinica chimica acta, 2017)
The relationship between increased serum enzyme activity of prolidase and increased rate of collagen turnover in the arterial wall has been asserted in previous studies. Collagen reflects much of the strength to the connective tissue involved in the arterial wall. Atherosclerosis is very common vessel disease and oxidative stress plays a pivotal role in the etiopathogenesis. Our objective was to examine the serum enzyme activity of prolidase and its possible relationships with oxidative stress parameters in obese subjects. Our present study was conducted 27 obese subjects and 26 age-matched healthy control subjects. The serum enzyme activity of prolidase in all study population was evaluated spectrophotometrically. Oxidative stress levels in obese subjects were analyzed with total antioxidant capacity (TAC) and total oxidant status (TOS) as well as oxidative stress index (OSI). Obese subjects have higher serum TOS and OSI indicators as well as prolidase activity than those in control subjects (for all; p<0.001). Moreover, obese subjects have lower levels of TAC than in those in healthy subjects (p<0.001). In the Pearson's correlation analysis, enzyme activity of prolidase was positively related with TOS (p<0.001, r=0.529) and OSI (p<0.001, r=0.519) as well as BMI (p<0.001, r=0.692) and inversely related with TAC (p<0.05, r=−0.405) in obese subjects. Increased serum prolidase activity and decreased antioxidant levels are likely to be a results of increased of oxidative stress levels in obese subjects. The significantly correlation between increased oxidative stress and increased prolidase activity may play a pivotal role in etiopathogenesis of atherosclerotic cardiovascular diseases in obese subjects. •Prolidase activity was found highly in obese subjects.•Serum prolidase activity was significantly higher in obese subjects than controls.•Obese subjects have increased oxidative stress and prolidase activity.